Pyoderma gangrenosum associated with ulcerative colitis and tuberculosis brain abscess successfully treated with intravenous immunoglobulin - G S Nayanathara; Varadraj Vasant Pai; Rakhi Ghodge (Wolters Kluwer Medknow Publications, 2024)
Pyoderma gangrenosum (PG) is a rare noninfectious autoinflammatory neutrophilic dermatoses occurring in 5%-12% of patients with ulcerative colitis (UC). Clinically, it is classified into ulcerative, pustular, bullous, and vegetative types. A few atypical and rare variants have also been described. The disease is characterized by painful cutaneous ulcers and is often associated with systemic diseases. Inflammatory bowel disease may precede it, follow it or occur simultaneously with PG. In some patients, control of bowel disease also leads to control of PG, but this does not occur in all patients. The mainstay of treatment is long-term immunosuppression with corticosteroids or ciclosporin. Herein, we present a case of PG associated with UC in whom immunosuppressants are contraindicated, was treated successfully with IV immunoglobulins.